2023
DOI: 10.3390/atmos14050854
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Variation of Summer Extreme Heat Events in the Beijing–Tianjin–Hebei Region

Abstract: Extreme heat events are frequent in the Beijing–Tianjin–Hebei (BTH) region due to global warming and accelerated urbanization. While previous studies have analyzed the trend of extreme heat events in the Beijing–Tianjin–Hebei (BTH) region, the interdecadal changes of these events remain unclear. Therefore, this study aims to analyze the interdecadal temporal and spatial characteristics of summer extreme heat events in the BTH region using daily mean and maximum temperature datasets from 174 stations over the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…It was observed that from 2019 to 2021, the majority of months with the highest frequency of ozone pollution in the region were concentrated in June. Therefore, the month of June was predominantly identified as the period with the greatest number of ozone content exceedances in the NCP, primarily associated with the prevalence of high temperatures, intense ultraviolet radiation, and scant rainfall in most areas of Beijing, Tianjin, and Hebei during this month [46][47][48]61,62]. Additionally, the peak levels of ozone pollution along the coastal regions of Hebei, Tianjin, and Shandong in 2019 and 2021 were noted to occur in May.…”
Section: The Spatiotemporal Patterns Of the Exceedances Of The Estima...mentioning
confidence: 99%
See 3 more Smart Citations
“…It was observed that from 2019 to 2021, the majority of months with the highest frequency of ozone pollution in the region were concentrated in June. Therefore, the month of June was predominantly identified as the period with the greatest number of ozone content exceedances in the NCP, primarily associated with the prevalence of high temperatures, intense ultraviolet radiation, and scant rainfall in most areas of Beijing, Tianjin, and Hebei during this month [46][47][48]61,62]. Additionally, the peak levels of ozone pollution along the coastal regions of Hebei, Tianjin, and Shandong in 2019 and 2021 were noted to occur in May.…”
Section: The Spatiotemporal Patterns Of the Exceedances Of The Estima...mentioning
confidence: 99%
“…Among these four seasons for the averaged MDA8, as shown in Figure 4a-d, O 3 pollution was highest in summer, followed by spring, then autumn, and the O 3 pollution was the lowest in winter. This is mainly due to the fact that during summer, the ultraviolet radiation is the strongest and the temperature is the highest, which is suitable for the photochemical reaction for the generation of ozone [46][47][48]. From the perspective of the spatial pattern of O 3 pollution, the most serious O 3 pollution area is in the border area of Hebei, Shandong, and Henan Provinces, that is, the southern part of Hebei, the northern part of Henan, and the western part of Shandong.…”
Section: Spatiotemporal Distribution Of the Estimated Mda8 In The Ncpmentioning
confidence: 99%
See 2 more Smart Citations